2020
DOI: 10.1108/sej-05-2020-085
|View full text |Cite
|
Sign up to set email alerts
|

Guest editorial

Abstract: The creative economy is deadlong live the creative-social economies Introduction: defining the field In this paper, we discuss the possible evolution from the creative industries (CIs) and creative economy (CE) towards creative-social economies (CSE). However, before explaining why we believe there is an increasing overlap between these two areas of research and policy intervention, it is crucial to define the two areas separately and consider the definition and critical aspects of each field of research.Creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Our findings build on previous research, which highlight the central role that higher education institutions play in developing local and regional economies (Comunian et al, 2020; Hauge et al, 2018) and add to the discussions that highlight the ways in which higher education institutions and the cultural creative industries interact (Comunian and Gilmore, 2014; Gilmore and Comunian, 2016). We extend this discussion by broadening current conceptions of what higher education institutions might look like and how they might change during interaction with surrounding environments.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 85%
See 2 more Smart Citations
“…Our findings build on previous research, which highlight the central role that higher education institutions play in developing local and regional economies (Comunian et al, 2020; Hauge et al, 2018) and add to the discussions that highlight the ways in which higher education institutions and the cultural creative industries interact (Comunian and Gilmore, 2014; Gilmore and Comunian, 2016). We extend this discussion by broadening current conceptions of what higher education institutions might look like and how they might change during interaction with surrounding environments.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 85%
“…Previous research has shown the various ways in which higher education institutions interact and shape the local communities they reside in (Comunian et al, 2013;Madichie and Agu, 2023). Fostering innovation and technological development (Gunasekara, 2006), higher education has been cast as central cultural and economic players in their local communities ( Åstebro and Bazzazian, 2011;Comunian et al, 2020). Whereas most of these studies focus on the role of higher education in relation to technological development (Lundvall, 2016;Mayer, 2007), a growing stream of research has made efforts to capture the various ways in which higher education and the cultural creative industries interact (Comunian and Gilmore, 2014;Gilmore and Comunian, 2016).…”
Section: Theoretical Framingmentioning
confidence: 99%
See 1 more Smart Citation
“…Al respecto, se está en un punto de inflexión en el cual gestión cultural ha iniciado un salto adaptativo hacia lo que se ha llamado Economía Social Creativa (Comunian, Rickmers y Nanetti, 2020). Dado el carácter social de la gestión cultural, los esfuerzos de adaptabilidad deben de enfocarse en la cooperación antes que en la competición.…”
Section: Innovación Social Y Ciencia Ciudadana En La Gestión Del Patrimonio En Un Escenario Post Covid-19unclassified
“…Like other industrial sectors, also the CCIs are adopting sustainable practices to green their value chain: as highlighted by a recent report of EIF-KEA (2021), CCIs are rethinking ways cultural products and services are produced and consumed by adopting more sustainable practices. Overall, we see a significant shift - especially after the 2008 global financial crisis - towards creative-social economies (Comunian et al, 2020) and towards engagement with environmental issues (Oakley and Banks, 2020). For example, recycled materials are more used in production processes; plastic bottles are replaced by more eco-friendly solutions during cultural events; saving energy lighting systems are implemented in museums and other cultural spaces; certifications like the Creative Green Certification explicitly designed for the arts and CCIs by Julie’s Bicycle 1 are more and more diffused; the fashion industry is implementing eco-friendly practices in the production system and thinking about extensive products’ lifecycle (cf.…”
Section: Introductionmentioning
confidence: 99%